Long-term kidney and systemic effects of calorie restriction in overweight or obese type 2 diabetic patients (C.Re.S.O. 2 randomized controlled trial). (March 2022) - Ruggenenti, Piero; Cortinovis, Monica; Trillini, Matias; Parvanova, Aneliya; Abbate, Manuela; Satriano, Chiara; Salvetti, Ferdinando; Bossi, Antonio C.; Trevisan, Roberto; Perna, Annalisa; Peracchi, Tobia; Rubis, Nadia; et al.
Highlights: In patients with T2D and obesity, calorie restriction ameliorated hyperfiltration. This effect translated into a relative long-term stabilization of kidney function. In this population calorie restriction improved many cardiovascular risk factors. Abstract: Aims: In type 2 diabetic patients with obesity, hyperfiltration is a risk factor for accelerated glomerular filtration rate (GFR) decline and is ameliorated by calorie restriction (CR). We assessed whether CR-induced amelioration of hyperfiltration could translate into slower long-term GFR decline in this population. Methods: In this academic, single-center, parallel-group, prospective, randomized, open-label, blinded endpoint trial, consenting >40-year-old patients with type 2 diabetes, BMI ≥27 kg/m 2, creatinine <1.2 mg/dL and albuminuria ≤300 mg/24 h were randomized (1:1) to two-year 25% CR (n = 53) or standard diet (SD, n = 50). Primary outcome was 6-month measured GFR. Analyses were by modified intention-to-treat. Results: At 6 months GFR decreased by 5.16 ± 10.03 mL/min ( P  = 0.001) with CR, and by 0.98 ± 9.71 mL/min ( P  = 0.497) with SD. Between-group difference was significant ( P  = 0.044). GFR decline from 6 to 24 months was significant with SD ( P  < 0.01), but not with CR ( P  = 0.075). Between-group difference, however, was not significant ( P  = 0.414). Body weight, BMI, waist circumference, systolic blood pressure, HbA1c, blood glucose, serum triglycerides decreased and ApoA-I concentration increased with CR. No changes were observed with SD. Between-group differences were significant. CR was tolerated well. Conclusions: In obese type 2 diabetic patients, CR ameliorated glomerular hyperfiltration and several cardiovascular risk factors, and blunted long-term GFR decline. Trial registration: NCT01930136.